The development of future foreign language teachers’ digital competences in creating multimedia tutorials - G. Zh. Smagulova; G. B. Sarzhanova; G. K. Tleuzhanova; N. Stanciu (Образование и наука)
Introduction. The article considers the problem of the development of future teachers’ digital competences in creating foreign language multimedia tutorials and presents the results of the corresponding research conducted by the authors. In the context of the digitalisation of education, the foreign language multimedia tutorials represent an effective means of organising and integrating authentic audio-visual materials into the learning process. Nevertheless, FL (foreign language) teachers today face the problem of the lack of the competences, including digital ones, necessary for the development of effective multimedia tutorials, which cannot be created without the awareness of the methodological foundations of their designing, mastering of the relevant software tools and obtaining the corresponding level of digital skills of their usage.Aim. The current research is aimed to identify the effectiveness of the training course for future teachers in the development of foreign language multimedia tutorials based on authentic audio-visual materials. The training course was conducted at Academician E. A. Buketov Karaganda University among 30 graduate students.Methodology and research methods. The research work was based on the determination of four levels of training in the field of development of multimedia foreign language tutorials: recognition-based, reproductive (adaptive), heuristic, creative.Results and scientific novelty. The developed training course proved its effectiveness in increasing the level of development of digital competences of future FL teachers in the field of designing multimedia educational resources. The research results demonstrated that 80 % of the participants achieved the heuristic level in the field of the development of digital educational resources, namely multimedia tutorials, getting the required 60 % and more points (according to Bespalko V. P.) in the final assessment of academic achievement.Practical significance. The corresponding authoring experimental training course contributes to solving the problem of the development of the future FL teachers’ competences when creating multimedia educational resources, and to the problem of skills formation when using appropriate software to create multimedia educational resources.